2022
DOI: 10.3390/ijerph19084782
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Psychiatric Drugs in Primary Care during the COVID-19 Pandemic

Abstract: Background: The main objective of this research was to analyze whether there were changes in the use of antidepressants, anxiolytics, and hypnotic-sedative drugs, in the context of primary health care, during the COVID-19 pandemic compared to the pre-pandemic period. We further sought to study consumption in vulnerable population groups. Methods: A cross-sectional observational study was performed in a primary health district of Spain. The data were obtained from the Andalusian Public Health System database, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
4
15
0
4
Order By: Relevance
“…Regarding age, consumption is higher for older age groups. These results are similar to those reported on a study by Gonzalez-Lopez 25 , with data from another Spanish region, Andalusia.…”
Section: Discusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding age, consumption is higher for older age groups. These results are similar to those reported on a study by Gonzalez-Lopez 25 , with data from another Spanish region, Andalusia.…”
Section: Discusionsupporting
confidence: 92%
“…Several hypothesis that can explain the higher consumption rates for women can be found in the literature, ranging from hormonal differences in life course (menstruation, pregnancy, menopause…), more medical consultations 26 , to gender inequalities regarding the double working shift, and their role of caregivers, which would translate into more psychological stress and explain higher prevalence of anxiety, depression, and sleep and eating disorders in women. 8,25 Our results, as in several studies 25,27 , show psychotropic consumption increases with age in both genders. A plausible explanation for this would be chronic disease and comorbidities that come with aging, alongside cognitive decline.…”
Section: Discusionsupporting
confidence: 89%
“…We found that 44.9% of long-COVID-19 subjects in have used BZD and Z-hypnotics, with women showing higher percentages. Benzodiazepine and Z-hypnotics use in the general population has significantly increased in Spain during the COVID-19 pandemic, with values ranging from 6.3 to 7.9% for anxiolytics, and 4.8% for hypnotic-Sedatives ( 22 , 23 ). Data from the Spanish Agency of Medicine and Health Products ( Agencia Española de Medicamentos y Productos Sanitarios , AEMPS) in a report on the use of anxiolytic and hypnotic drugs in Spain showed consumption increasing from 90.60 defined daily dose/1,000 inhabitants per day (DHD) in 2019 to 93.04 DHD in 2020 ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was not observed in women with long-COVID-19. Different researches performed during the pandemic have demonstrated that psychotropic drug consumption rises with age, particularly after 65, in both men and women ( 15 , 16 , 23 ). One possible explanation for our results is that long-COVID-19 subjects in our study was a young population, with only 19% of the sample older than 55.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that before the COVID-19 outbreak, being of student age was associated with the highest frequency of stimulants use [ 9 , 10 ]. Moreover, the use of, for example, sedatives—such as antidepressants, anxiolytics and hypnotic-sedatives—has increased due to pandemic-related mental distress [ 11 ]. Interestingly, the consumption aspect needs to be considered bearing in mind that sedatives are taken disparately in various areas, which generally reflects the problem with the usage of drugs overall [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%